Leadership Character in the Social Science Subject Theme “My Hero” of the 4th Grade at State Elementary School Purwomartani Kalasan Sleman Yogyakarta - Asnafiyah Asnafiyah (Tarbawi, 2020)
This study aims to describe the learning of leadership characters in the 4th grade social science subject at state elementary school Purwomartani, Kalasan, Sleman, Yogyakarta. This was done because Indonesia seems to have lost its good leadership character which could become an example for children. This research is qualitative with data collection using observation, interview, and documentation techniques. Data analysis was performed through data reduction, data presentation, verification, and conclusion. The results showed that there are several leaders discussed in the 4th grade textbook of elementary school with the theme "My Hero" in social sciences subject. These leaders have different leadership characters, namely (1) the courage to defend truth, justice and expel colonialism are the characters of Prince Diponegoro, Sultan Hasanuddin, Cut Nyak Din, and Pattimura, (2) the spirit to unite the nation is a character of Gadjah Mada and Soekarno, (3) being persistent in teaching and establishing educational institutions are character of Ki Hajar Dewantara, (4) struggling to never give up and being willing to sacrifice to defend Indonesia's independence are the character of Bung Tomo, and (5) being able to realize the objectives of Indonesia's independence and inspire the younger generation are the character of President Soekarno. These findings have implications for learning social science subject with the theme of my hero, beginning with telling the leadership characters of the figures to be role models for students in their life.